Doctor appointment application: a user experience experiment - Omar, Firas (International Journal of Engineering and Technology, 2018)
Designing an application with elevated usability is the aim of the study. The more usable, more positive user experience we are achieving.The medical field is currently experiencing low UX applications and interfaces. The study will strive to address the healthcare systems in Jordan.While taking the user into our consideration and giving what he/she might find usable and enjoyable a high priority, only by such approach we will succeed and achieve a positive user experience.Â Â